The Application of Using Picture Media for Improving the Students’ Achievement In Writing Descriptive Text (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2025)
The purpose of this research is to find out the application of using picture media for improving the students’ achievement in writing descriptive text at the eighth grade of SMP Swasta Kartika 1-4 Pematangsiantar. This research used a quantitative approach with a true experimental method design. The population of this research was eighth grade students consisting of 68 students from 2 classes, and all were used as the sample through saturated sampling technique. The data collection technique was pre-test and post-test. The data were analyzed using SPSS version 27.0. The result of the research showed that the hypothesis testing of post-test control class and post-test experimental class shows that that tcount = 3,022 > ttable = 1,695. This means that H0 is rejected and H1 is accepted. The post-test score was significantly higher than the pre-test score, indicating that the use of picture media effectively improved students' achievement in writing descriptive texts. This can happen because the researcher provides treatment in the experimental class, namely explaining about descriptive text, generic structure, tenses used, and examples of descriptive text. The researcher also asks students to create descriptive text like the example given. Not only that, the researcher also explains how to use picture in creating descriptive text, then the researcher asks students to create descriptive text according to the image. When students understand, the researcher provides another picture and asks students to create descriptive text based on the image